Alice Austen lived here - Gino, Alex (Scholastic Press, 2022)
Seventh-grade nonbinary best friends Sam and TJ explore the borough of Staten Island in New York to complete a history assignment for school. Instead of choosing a "Dead Straight Cisgender White Man" to study, they decide to explore queer history in the area and learn about lesbian photographer Alice Austen. As they set out to uncover more information on Austen, Sam also learns more about their identity, their relationships, and the importance of mentors and community.